The Efforts of Talang Mamak Indigenous People to Maintain Their Existence in Customary Forest Resources Battle: The Efforts of Talang Mamak Indigenous People to Maintain Their Existence in Customary Forest Resources Battle - Rizky Octa Putri Charin; Arief Hidayat (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
The resources of Customary Forest play an important role for Talang Mamak Indigenous People to survive. The exploitation of the forest by private company and investor has caused a violent conflict. The situation of the indigenous people becomes worsen since local government does not fully protect their rights on the forest. Even, Local government tends to defend private company and investor in addressing the conflict. Customary forest of Talang Mamak indigenous people is in the oligarchs grip and conflict of interest with their elder. The Indigenous people are in crossroad, to preserve or to release their heritage and right. This study aims to determine the efforts of Talang Mamak Indigenous People to maintain their existence in the customary forest resources battle with private company and investor. This study used qualitative descriptive method. The data collection were documentation analysis and other relevant literature. This study used Theory of Oligarchy (Winters 2011) as grounded theory. The result found that the efforts of the indigenous people to fight for their rights getting weak. Some of them begin to accept compensation from the company and investor, in other word, some of them are willing to release their heritage and right on the forest.